Lignanes from the Brazilian Melia azedarach, and their activity in Rhodnius prolixus (Hemiptera, Reduviidae) - Cabral, Marise M. O. (1995)
Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Departamento de Bioquímica e Biologia Molecular. Rio de Janeiro, RJ, Brasil.